Peningkatan keterampilan membaca pemahaman melalui metode preview, questions, read, reflect, recite, review (PQ4R) pada peserta didik sekolah dasar di Surakarta. - Isma Herminingsih; Hartono Hartono; Karsono Karsono (Didaktika Dwija Indria, 2020)
The aim of this research is improving reading comprehension skill through PQ4R method. The type of this research is Classroom Action Research which held in 3 cycles. The first and second cycles held in two meetings while the third cycle only one meeting. This study takes research subjects from teacher and 3th students in one of elementary in Surakarta. This study uses interview, observations, tests, and documentation as techniques in collecting data. Data was validated using triangulation techniques and triangulation sources. Data was analyzed using Miles and Huberman models. The results of the first cycle of action obtained by 53% classical completeness, increased in second cyecle with 81% classical completeness and third cycle with 90%. The study was stopped in third cycle because the research performance indicators had been reached. Based on these result, it can be concluded that there is an increase in reading comprehension skill in 3th grade students after applying the method of Preview, Question, Read, Reflect, Recite, Review (PQ4R) in learning process.